What’s in a name? An enquiry about the interpretation of Agama Hindu as “Hinduism” - Michel Picard, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
In this article, I question the conceptual categories of “religion”, “agama”, “dharma”, and “Hinduism”, in order to investigate through which processes and within which contexts the Balinese religion resulted in being construed as agama Hindu. After having investigated how the Sanskrit loanword agama came to designate in Indonesia an Islamic conception of what “religion” is about, I assess the similarities between the construction of Indian Neo-Hinduism and the interpretation of the Balinese religion as agama Hindu. In particular, I pay attention to the controversy which has been dividing the Balinese intelligentsia over the proper name of their religion, as it reveals a perennial conflict between the Balinese who want to retain the specificity of their customary ritual practices, and those who aspire to reform the Balinese religion by conforming it to what they think Hinduism is about.
Keywords: Religion; agama; dharma; Hinduism; agama Hindu Bali vs agama Hindu